Assessing the Appropriateness of the EQ-5D for Duchenne Muscular Dystrophy: A Patient-Centered Study. (February 2021) - Crossnohere, Norah L.; Fischer, Ryan; Lloyd, Andrew; Prosser, Lisa A.; Bridges, John F. P.
Background: Duchenne muscular dystrophy is a rare degenerative neuromuscular disorder with pediatric onset. Recent approvals in Duchenne have placed attention on the economic evaluation in pricing and reimbursement decisions across a range of rare conditions. We sought to assess the appropriateness of the EQ-5D, a common measure of generic health state utility, for use among patients and caregivers affected by Duchenne. Methods: An international, cross-sectional sample of adults with Duchenne and caregivers reported patient health status using self- or proxy-reported EQ-5D-3L. Appropriateness was assessed across 6 domains of concern raised by stakeholders in Duchenne. These concerns were that the EQ-5D/EQ-VAS would not capture meaningful differences in health status, correlate with disease-specific measures, reflect real health status, exhibit face validity, be accurately interpreted, and be low burden. We evaluated these concerns by comparing EQ-5D index score and EQ-VAS scores to other condition-specific functional measures and open- and closed-ended questions. Results: In total, 263 participants (74% response) completed the survey, 24% of whom were adult patients. Most participants lived in the United States or United Kingdom (58%). Patient age ranged from 1 to 48 y. EQ-5D index was higher in ambulatory than nonambulatory patients (0.60 v. 0.30, P < 0.001) and was negatively correlated with upper limb impairment ( r = 0.61, P < 0.001). Three-quarters of respondents agreed that EQ-5D measured real health status (74%). Most respondents interpreted EQ-VAS anchors of best and worst imaginable health as full health (61%) and death/near death (58%). Respondents indicated the EQ-5D was easy to understand (86%) and answer (71%). Conclusions: Contrary to anecdotal concerns, we found support for the appropriateness of EQ-5D to assess health status in Duchenne. While other measures may be more sensitive to specific outcomes in Duchenne, there may be some value in results using the EQ-5D measure.